Antiretroviral Drugs Associated With Subclinical Coronary Artery Disease in the Swiss Human Immunodeficiency Virus Cohort Study. (8th April 2019) - Kovari, Helen; Calmy, Alexandra; Doco-Lecompte, Thanh; Nkoulou, René; Marzel, Alex; Weber, Rainer; Kaufmann, Philipp A; Buechel, Ronny R; Ledergerber, Bruno; Tarr, Philip E; ,
Abstract: Background: Coronary artery disease (CAD) events have been associated with certain antiretroviral therapy (ART) agents. In contrast, the influence of ART on subclinical atherosclerosis is not clear. The study objective was to assess the association between individual ART agents and the prevalence and extent of subclinical CAD. Methods: Coronary artery calcium (CAC) scoring and coronary computed tomography angiography (CCTA) were performed in ≥45-year-old Swiss Human Immunodeficiency Virus Cohort Study participants. The following subclinical CAD endpoints were analyzed separately: CAC score >0, any plaque, calcified plaque, noncalcified/mixed plaque, segment involvement score (SIS), and segment severity score (SSS). Logistic regression models calculated by inverse probability of treatment weights (IPTW) were used to explore associations between subclinical CAD and cumulative exposure to the 10 most frequently used drugs. Results: There were 403 patients who underwent CCTA. A CAC score >0 was recorded in 188 (47%), any plaque in 214 (53%), calcified plaque in 151 (38%), and noncalcified/mixed plaque in 150 (37%) participants. A CAC score >0 was negatively associated with efavirenz (IPTW adjusted odds ratio per 5 years 0.73, 95% confidence interval [CI] 0.56–0.96), tenofovir disoproxil fumarate (0.68, 95% CI 0.49–0.95), and lopinavir (0.64, 95% CI 0.43–0.96). Any plaque was negatively associated with tenofovir disoproxil fumarate (0.71, 95% CI 0.51–0.99). Calcified plaque was negatively associated with efavirenz (0.7, 95% CI 0.57–0.97). Noncalcified/mixed plaque was positively associated with abacavir (1.46, 95% CI 1.08–1.98) and negatively associated with emtricitabine (0.67, 95% CI 0.46–0.99). For SSS and SIS, we found no association with any drug. Conclusions: An increased risk of noncalcified/mixed plaque was only found in patients exposed to abacavir. Emtricitabine was negatively associated with noncalcified/mixed plaque, while tenofovir disoproxil fumarate and efavirenz were negatively associated with any plaque and calcified plaque, respectively. Abstract : In this prospective coronary computed tomography angiography study among human immunodeficiency virus–positive participants, noncalcified/mixed plaque was only positively associated with abacavir. Emtricitabine, tenofovir disoproxil fumarate, and efavirenz were negatively associated with noncalcified/mixed plaque, any plaque, and calcified plaque, respectively.